“I Sometimes Pretended to Get Groceries”: Restrictive Deterrence in Drug Dealing - Guo, Jing-ying (International journal of offender therapy and comparative criminology, 2023)
Despite steady progress in drug control work, drug-related crimes are ranked third in the total number of criminal cases in China. Based on in-depth interviews with 24 offenders who are now incarcerated for drug offenses, this paper examines the strategies employed by drug offenders to evade detection and mitigate their punishment for drug dealing. Their most frequently-used strategies focus on filtering out risky people, ensuring information asymmetry and knowing when to stop. Exploring how offenders adapt their behavior in response to punishment helps to further our understanding of crime commission and control.